2014
DOI: 10.4236/ijcm.2014.512088
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal Hernia Repair with Local Anesthesia in the Outpatient—10 Year Experience

Abstract: Objective: To demonstrate the feasibility of inguinal hernia repair with local anesthesia in an outpatient regime, with safety, efficacy and short learning curve. Methods: We prospectively evaluated 1186 patients undergoing inguinal hernia repair under local anesthesia on an outpatient basis between November 2004 and March 2014. Of the total number of hernias surgically treated in this period, 755 were operated on the right, 394 on the left and 37 bilateral. We used clinical, surgical and psychosocial criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A total of 46 studies reported mortality within 90 days. The studies covered 10 332 patients: 7976 had LA, 722 regional anaesthesia and 1634 GA. Methods of follow‐up included clinical examination, telephone call, questionnaire , contact with family doctor and electronic patient data management.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 46 studies reported mortality within 90 days. The studies covered 10 332 patients: 7976 had LA, 722 regional anaesthesia and 1634 GA. Methods of follow‐up included clinical examination, telephone call, questionnaire , contact with family doctor and electronic patient data management.…”
Section: Resultsmentioning
confidence: 99%
“…). A total of 53 studies were included: 12 RCTs and 41 cohort studies, with either a prospective or retrospective study design. Study characteristics are summarized in Table S1 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of anesthesia has significantly improved the treatment of inguinal hernia, significantly reducing recurrences, complications, recovery time and return to normal working activities. Hernia surgery should be approached according to a technique as simple and safe as possible that is at the same time accepted by the patient and easily realizable by the surgeon [ 1 , 2 ]. It is important find solutions which can be adapted to each individual patient, combining experience and new technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Hernia surgery should be approached according to a technique as simple and safe as possible that is at the same time accepted by the patient and easily realizable by the surgeon [ 1 ]. Inguinal hernioplasty is now the most performed surgery in the departments of general surgery [ 2 ]. For this reason it is necessary to find solutions which can be adapted to each individual case, combining experience and innovation.…”
Section: Introductionmentioning
confidence: 99%